Productive performance and egg quality in laying hens fed with four commercial sources of inorganic phosphate - Salinas C., Annie (2023)
The aim of the present study was to evaluate the productive performance of commercial laying hens supplemented with four commercial sources of inorganic phosphates for four weeks. In total, 960 Hy-Line Brown hens of 56 weeks of age were distributed in 4 treatments with 6 repetitions each and 40 hens per repetition. The treatments were: T1, Diet with dicalcium phosphate (DCP)-Peru; T2, Diet with DCP-China; T3, Diet with mono-dicalcium phosphate (MDCP)-Peru; and T4, Diet with mono-calcium phosphate (MCP)-China. The diets were formulated to contain 0.36% available phosphorus and the other nutrients according to the nutritional specifications of the genetic line. The percentage of egg production, egg mass, feed consumption and feed conversion were recorded. Also, egg weight, eggshell percentage, yolk and albumen percentage, eggshell thickness, specific gravity, eggshell colour, yolk colour and Haugh Units (UH). No significant differences were found due to the effect of the phosphorus source on egg weight, eggshell and yolk colour, while eggshell percentage, eggshell thickness, specific gravity, HU and yolk percentage were affected (p<0.05) for dietary treatments. It is concluded that the inorganic phosphate sources evaluated did not have a significant effect on the productive parameters, and that the eggs of the hens supplemented with DCP-China presented a higher specific gravity compared to the other sources of inorganic phosphate.